Recurrence of hamstring injuries and risk factors for partial and complete tears in the National Football League: an analysis from 2009-2020 - Bodendorfer, B. M.; DeFroda, S. F.; Newhouse, A. C.; Yang, D. S.; Shu, H. T.; Wichman, D.; Murphy, J. P.; Milnerb, J. D.; Hartnett, D. A.; Gould, H.; Chahla, J.; Nho, S. J. (The Physician and Sportsmedicine, 2023)
Purpose To (1) characterize hamstring injury (HSI) recurrence rates across the 2009-2010 to 2019-2020 NFL seasons and (2) to identify HSI recurrence risk factors among positions and determine the weekly return to play (RTP) recurrence risk. We hypothesized that older players, skill position players, and players returning to play faster were most at risk.